A Genre Analysis of the Undergraduate Thesis Abstracts: Revisiting Swales’ Theory of Written Discourse - Suwarni, Andi (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The genre analysis has become a critical study in pragmatic which forms the dialogic interaction that manifest written academic discourse socially and culturally. The aims of this study is to describe the pattern and variation of moves that appear from the undergraduate thesis abstracts at a specific college in the Bone Region. The implications of this study on educational written materials are included. Data collection comprised 45 abstracts as samples consist of 3 cohorts (2015, 2016 and 2017) of university students, each with 15 abstracts. A structure studied by Hyland (2005) was used to explain the different trends in the abstracts. Unstructured interviews with and evaluation of the students were carried out to better understand the writing skills of the students. Then data were analyzed using content analysis. The results show that most abstracts involve rhetorical gestures similar to the previous study. The moves include an initial statement, a clarification of intent and confirmation of the results and explanations for the research 's significance. The results also indicated that university students are more mindful of the logical series. Rhetorical movements and language properties needed in abstract academic learning. The aim, methodology and findings of the related paper are the most abstracts. These findings are compatible with previous studies and show that future scientists based on movement analysis that should explore the link between movement analysis results and academic teaching content. The results justify such pedagogic consequences that indicate that the student has an interest in current education research to change the teaching materials.